Lower estimated glomerular filtration rates in patients on long term lithium: a comparative study and a meta-analysis of literature - Rodrigo, Chaturaka; De Silva, Nipun Lakshitha; Gunaratne, Ravindi; Rajapakse, Senaka; De Silva, V.A.; Hanwella, Raveen (Springer Nature, 2014)
Background: Several studies have shown that long-term lithium use is associated with a subtle decline in estimated glomerular filtration rate. This study compared mean estimated glomerular filtration rates (eGFR) in patients on long term lithium, against matched controls. Methods: Patients with bipolar affective disorder, who are on lithium (for at least a year), were compared against controls that were matched (1:1) for age, gender and presence or absence of diabetes or hypertension. The eGFR was calculated from creatinine values according to the ‘modification of diet in renal disease study’ (MDRD) formula and was compared between cases and controls. A meta-analysis was performed to compare our findings with similar studies in literature. Results: Forty seven patients met the inclusion criteria. They were matched with 47 controls. The eGFR values of lithium users were significantly lower (p = 0.04) compared to controls. This difference persisted between the subgroup of lithium users without comorbidities (diabetes and hypertension) and their controls but disappeared for lithium users with comorbidities and their controls. Nonetheless, lithium users had lower eGFR values in both subgroups. A meta-analysis of 9 studies showed a significant lowering in the glomerular filtration rate in lithium users compared to controls [mean difference −10.3 ml/min (95% confidence interval: -15.13 to −5.55, p < 0.0001)]. Conclusions: Lithium causes a subtle decline in glomerular filtration rate; renal function needs to be monitored in patients on lithium treatment.
Keywords: Lithium; Chronic Kidney Disease; Glomerular Filtration Rate; Acute Kidney Injury; Neuroleptic Malignant Syndrome